Measurement of muonic X-rays using a segmented calorimeter towards an observation of parity violation in muonic atoms - Dr Sohtaro Kanda; Dr Katsu Ishida (ISIS Facility, 2019)
The proposed experiment aims to establish a detector system for a measurement of parity-violating effect in muonic atoms. A measurement of parity violation in atoms is a precision test of the standard model of particle physics via the determination of the Weinberg angle at low-energy scale. Furthermore, atomic parity violation in muonic atoms provides a unique opportunity to search for an unknown particle coupling to the muon. Parity violation in muonic atoms can be observed by a detection of x-ray emission associated with a parity-odd transition. In order to observe the process with small branching-ratio, a dedicated x-ray detector is necessary. The detector consists of inorganic scintillator crystal, silicon photomultiplier, and fast readout electronics. In the proposed experiment, energy and timing resolution and high-rate capability of the detector are evaluated.
Keywords: STFC ISIS Neutron and Muon Data